Preliminary Study on the Accessibility and Learning Experience of Low-Code Development Platforms - Theam Lim, Jit; Kang Lee, Chen; Heng Lim, Ean; Voon Wong, Pei; Tak Yew, King; Yee Ooi, Chek (2024 5th International Conference on Artificial Intelligence and Data Sciences (AiDAS), 2024)
The Computer Science education industry faces challenges in traditional computer science education that depends critically on theoretical programming concepts and application development activities. This learning approach's lack of practical experience can be a hurdle for contemporary computer science students. Hence, this research is to study the integration of multiple tools and approaches, including low code development platforms (LCDP), so educators can empower students, even those without prior programming experience, to actively engage in software development processes and grasp programming concepts quickly. The questionnaire is used in the pilot study. 40 sets of questionnaires were distributed to the computing students, and 37 (92.5%) respondents completed the questionnaires. This research uses the descriptive technique to assess the computing students' responses to the accessibility and learning experience of low-code development platforms. The data analysis findings from the pilot study demonstrated a positive significant learning experience with low-code development platforms, as perceived by the respondents. Findings also show that over two-thirds of the respondents find the learning experience of using low-code platforms is easier than the traditional approach. Therefore, the finding implies that adopting low-code development in tertiary computing education could lead to a significant paradigm shift in how programming is taught and learned.